Macron, the Yellow Vests and the national debate: Playing for time, not solving the political legitimacy crisis - Ronja Kempin; Paweł Tokarski (Stiftung Wissenschaft und Politik (SWP), 2019)
France's yellow vests (gilets jaunes) are heterogeneous, make contradictory demands, and refuse to give up. Since November 2018 they have been demonstrating for more purchasing power and greater democracy. Having made financial concessions, President Emmanuel Macron is now playing for time. He has initiated a 'grand national debate', in which all citizens were called on to voice their opinions concerning future political issues. This debate is likely to help him win the European Parliament (EP) elections in May and facilitate splintering the yellow vests. To avert further protests that could paralyse the country, delegitimise his government and ensure that his presidency fails, Macron needs to improve the way he communicates his reform agenda. Merely playing for time will not make France reformable and governable for this president, any more than it did for his predecessors.
Keywords: 320